Realisme dalam Filsafat Pendidikan: Landasan Materiil dalam Pembentukan Kurikulum - Adyputri, Nur Nazhifah; Ismail (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The philosophical foundation of realism and its implications for education, with a focus on curriculum development in Indonesia. The lack of a philosophical basis in curriculum design often neglects realism’s emphasis on objective reality as the true source of knowledge. The purpose of this study is to analyze how realism influences educational goals, curriculum structure, learning methods, and the roles of teachers and students, while also examining its relevance to the Kurikulum Merdeka (Independent Curriculum). This study employs a qualitative method with a literature review approach, examining classical works of philosophers such as Aristotle and secondary sources such as journals and recent research. The analysis is conducted using a descriptive-critical technique to explore the ontological, epistemological, and axiological aspects of realism. The findings indicate that realism asserts the existence of a reality independent of human thought and positions factual and scientific knowledge as the foundation of education. A realism-based curriculum is comprehensive, encompassing science, mathematics, humanities, social sciences, and values, with logical, psychological, and habituation methods. Teachers act as facilitators and classroom managers, while students are expected to master knowledge, maintain discipline, and think rationally. This study concludes that integrating realism into the Kurikulum Merdeka provides a strong epistemological foundation for fostering critical thinking, analytical skills, and problem-solving abilities essential for addressing modern challenges.